The Role of Fibre Intake in Combination With Physical Activity in Reducing Body Composition Parameters. (14th June 2022) - Khawandanah, Jomana; Chambers, Edward; Frost, Gary
Abstract: Objectives: To investigate the dual effect of physical activity and fibre intake on body composition parameters in males and females. This study hypothesises that the relationship between body composition parameters and fibre intake is dependent on physical activity and gender. Methods: This study included 8958 individuals (5438 males and 3520 females) from the Airwave Health Monitoring Study, which uses the International Physical Activity Questionnaire (IPAQ) to categorise Physical Activity Levels (PAL) into low (PAL 1.4), medium (PAL 1.6) and high (PAL 1.8) 1, 2 . Dietary fibre intake was measured by 7-day food records 3 . The effect of physical activity and fibre consumption on four body composition parameters: BMI, body weight, waist circumference and body fat% was investigated using ANOVA with Bonferroni correction. Results: There were significantly lower values for all tested body composition parameters in the highly physically active group (PAL 1.8; n = 4464) compared to the least physically active group (PAL 1.4; n = 1388) after adjustment for age, gender and energy intake. PAL 1.8 participants were categorised into quartiles of dietary fibre intake. After adjusting for age, gender, energy intake and total Mets (amount of energy expended carrying out physical activity), we found that those with the highest daily fibre consumption (³13g/ 1000 kcal; n = 1136) had a mean of 0.5 kg/m 2 (BMI; SE = 0.2, p = 0.014), 1.1kg (body weight; SE = 0.8, p = 0.059), 2.4 cm (waist circumference; SE = 0.6, p < 0.001) and 1.6% (Body Fat%; SE = 0.4, p < 0.001) lower than those with lowest fibre consumption (≤6.1 g/1000 kcal,  n = 1088) (table2). When separate gender analysis was conducted, the difference in the four measurements between the groups with highest and lowest fibre intake was significant in males only (BMI: 0.9 kg/m 2 ; SE = 0.2, p < 0.001, body weight: 2.4 kg; SE = 0.9, p = 0.002, waist circumference: 3.1cm; SE = 0.7, p < 0.001, body fat%: 2.3%; SE = 0.4, p < 0.001). Conclusions: The present study is the first to examine the impact of dietary fibre intake on body composition measures in physically active adults. The study shows that dietary fibre consumption is capable of improving body composition in physically active individuals, however, this effect was driven by changes in males. Funding Sources: Imperial College London, London, W12 0NN, UK.